UPAYA UNIT DIKYASA MELALUI PROGRAM POLICE GOES TO SCHOOL DALAM MENGURANGGI PELANGGARAN LALU LINTAS DI KALANGAN PELAJAR - Dohan Yoanda Prima (Advances in Police Science Research Journal, 2020)
The focus of this thesis research is about the efforts of the Unit Under the Police Program to Go to School in Reducing Traffic Violations Against High School Students in Cimahi Regional Police. Regarding the problems raised in this thesis research, namely: (1) How the efforts of the Police Go to School Program carried out by the unit are assumed to reduce traffic ties in the cimahi police area, (2) What is related to the Goes To Police program School that encourages high school student traffic in the cimahi police precinct To analyze these problems, researchers used a qualitative approach with field and research methods holistically. The use of conceptual framework in the form of theory and concepts is used as a knife of analysis by researchers in answering the formulated problems. Theories and concepts used by researchers are communication management theory, police goes to school concepts of operational definition, The findings during this study are (1) There are still many Respect Factors so that the implementation of the program is still not optimal (2) There are still complaints from the school against the police goes to school program. (3) The efforts made by the Cimahi Regional Police in the Sat section have not yet been maximized examples: 1. Lack of technology utilization, 2 Coordination with other functions is still rare 3. SOPs used as guidelines have not yet been embedded.